Comparison of pathology in susceptible A/J and resistant C57BL/6J mice after infection with different sub-strains of Plasmodium chabaudi - Hernández Valladares, M.; Naessens, Jan; Nagda, S.M.; Musoke, A.J.; Rihet, P.; Ole-MoiYoi, O.K.; Iraqi, F.A. (Elsevier, 2004)
Susceptible A/J and more resistant C57BL/6J mice were infected with Plasmodium chabaudi chabaudi 54X, P.c. chabaudi AS and Plasmodium chabaudi adami 408XZ. As expected, most C57BL/6J mice survived the infections with the different isolates. But in contrast to previous observations, not all A/J mice succumbed to infection: just over 50% of A/J mice survived infections with P.c. chabaudi 54X, while 80% survived P.c. chabaudi AS. The more virulent parasite, P.c. adami 408XZ, was able to kill all A/J mice and 20% of C57BL/6J mice after an intravenous infection with 105 pRBC. A detailed study of four parameters of pathology (body weight, body temperature, blood glucose and RBC counts) in both mouse strains after a P.c. adami 408XZ infection showed similar patterns to those previously reported after infection with P.c. chabaudi AS. These data suggest that environmental factors as well as parasite polymorphisms might influence the severity of malaria between susceptible and resistant mice.